The Prentice Hall guide to research writing - "Memering, Dean,"; "Memering, Dean, 1936- Research writing." ("Englewood Cliffs, N.J. :")
First ed. published as: Research writing. c1983. Includes index.
Keywords: REPORT WRITING.;RESEARCH.